PEMAHAMAN NILAI MODERASI BERAGAMA MELALUI BUDAYA MENULIS DI SMK SELAGAN PONDOK LABU - Amaliyah Amaliyah; Deni Darmawan; Yenny Merintul Hasanah (PENGABDIAN SOSIAL, 2023)
ABSTRACT Understanding the value of religious moderation in schools for both teachers and students must be implemented in real life in the development of education. Religious moderation is also meant to prevent radicalism among students. The values of tolerance accept differences and diversity, especially in thinking, will be a development for science. One way to implement religious moderation is with a writing culture. Writing can give you the feel of being open about what is on your mind. As a form of informing government programs related to religious moderation. And develop student literacy programs. So through Community Service (PKM) Pamulang University at Selagan Pondok Labu Vocational School, invites teachers and students to build religious moderation in schools and conduct writing training. Appreciation of teachers, students especially the school in the activities of providing smooth PKM activities Keywords: Religious Moderation, Writing Culture